The myth of Methuselah and the uncertainty of death: The mortality fan charts - Kevin Dowd; David Blake; Andrew J. G. Cairns (Risks, 2016)
This paper uses mortality fan charts to illustrate prospective future male mortality. These fan charts show both the most likely path of male mortality and the bands of uncertainty surrounding that path. The fan charts are based on a model of male mortality that is known to provide a good fit to UK mortality data. The fan charts suggest that there are clear limits to longevity-that future mortality rates are very uncertain and tend to become more uncertain the further ahead the forecast-and that forecasts of future mortality uncertainty must also take account of uncertainty in the parameters of the underlying mortality model.
Keywords: 330; mortality; fan charts; longevity risk; parameter risk